OPTIMIZATION DISTRIBUTION ROUTES AND DELIVERY COSTS WITH TRANSPORTATION AND SAVING MATRIX METHODS - Gama Aziiz Priyambodo; Muhammad Aldi Hamdani; Thariq Ghufrani Akbar; Adi Teguh Suprapto (Universitas Bunda Mulia, 2020)
This study aims to determine the distance traveled to each targeted area by optimizing the cost and delivery routes by saving matrix method and transportation at PT Herona Express. The method used is qualitative method by observation and interview. Data collected then processed by analysis of relationship between variables by using transportation method of calculation of QM for Windows and saving matrix method from processing data in get minimum result in cost of delivery to every area will be visited the data in order to minimize costs incurred by PT Herona Express and can estimate the time and distance that will be taken each time the process of delivery based on saving matrix results obtained Transport cost savings after the application of Saving Matrix methods are: obtained total transportation costs on the route the initial cost of Rp 1,017,125 / day or Rp 371,250,625 / year and the cost after the application of saving matrix method obtained the total transportation cost on the route from 1 to 3 of Rp 660.004 /day or Rp 240.916.060 / year so obtained transportation cost savings tasi Rp 357.081 /day or Rp 130.334.565 / year or 35.1% transportation cost savings. Keywords: Cost, Delivery Routes, Transportation, Saving Matrix